The Effect of Perceived Customer Effectiveness of Green as Moderator Variable on Eco-Friendly Practices, Green Image and Customer Attitudes in a Canteen at University of Surabaya - Rahardja, Christina; Anandya, Dudi; Setyawan, Andhy (Jurnal Aplikasi Manajemen, 2018)
This study aims to examine the relationships customers’ perceived green practices, perceived the green image of a canteen, and attitudes toward a canteen, Keluwih customers and identifies the key green practices that influence customers’ perceptions of a canteen’s green image. The model used for this study adopted from Jeong et al. (2014). The respondents came from the employee, lecturer, and students of University of Surabaya with total 200. Data were analyzed using SEM with AMOS 18. First, the results suggest the perception of green practices affects customers’ perceived green image of a canteen which in turn influences customers’ attitudes toward a canteen. Second, the moderation of PCEG group in the research model between the group of Less Green and Green is not supported.In Less Green group, there is an indirect influence ofenvironmentally friendlypractices on the behavior through the mediation of the image of Keluwih canteen with environmentally friendly. In Green group, there is a direct influence of environmentally friendly practices on the consumers’ attitude of Keluwih canteen. Finally, the paper includes a theoretical model that helps explain customers’ formation of a green image and attitudes toward a canteen Keluwih and offers practical guidelines for effective green marketing management in canteen Keluwih management.